ENGINE DEVELOPMENT AND PROCUREMENT OF SIGN LANGUAGE: A SEARCH FOR RELATIONSHIPS (Fiep Bulletin - online, 2011)
Communication between humans is a necessity and phylogenetic brand stores information that linguistic, cultural and social group. The research examined the difficulties in acquiring language from the comparative study with two groups of learners LIBRAS Federal Institute of Piauí, difficult to identify and characterize the relationship between language acquisition and motor development in the expression of gestural communication between users of LIBRAS. The sample consisted of 13 subjects in experimental research, and as a means of collecting data on a semi-structured. The study found the need to implement public policies that include public, through integration of the discipline LIBRAS in school and university curricula, development of exercise program to improve hand motor coordination of language users.
Keywords: LIBRAS; motor development and communication